2018
DOI: 10.1111/1753-0407.12867
|View full text |Cite
|
Sign up to set email alerts
|

Social jetlag, sleep‐related parameters, and glycemic control in adults with type 1 diabetes: Results of a cross‐sectional study

Abstract: Background Social jetlag (SJL) is a small recurrent circadian rhythm disruption and the most frequent form of circadian rhythm misalignment. The main aim of this study was to investigate the effect of SJL on glycemic control, as assessed by HbA1c, in real‐life settings. Methods In all, 115 consecutive patients with type 1 diabetes (T1D) were analyzed cross‐sectionally. Data on bedtime, sleep onset latency, and wake up time on weekdays and weekends during the previous month were collected from all participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
1
17
3
Order By: Relevance
“…On the other hand, our results found no relationship between HbA1c levels and weekend sleep duration and social jetlag among college students with T1DM. The discrepancies between our finding and previous studies [24,43] could be due to our small sample size and lack of statistical power. Thus, more research with a larger sample size is warranted.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our results found no relationship between HbA1c levels and weekend sleep duration and social jetlag among college students with T1DM. The discrepancies between our finding and previous studies [24,43] could be due to our small sample size and lack of statistical power. Thus, more research with a larger sample size is warranted.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
“…Our results found no statistical gender differences among college students with T1DM, however, males selfreported longer sleep duration (weekdays and weekends) and increased napping and social jetlag. Also, social jetlag was associated with an increase in HbA1c among adults with T1DM [43] and T2DM [24]. On the other hand, our results found no relationship between HbA1c levels and weekend sleep duration and social jetlag among college students with T1DM.…”
Section: Discussion/conclusioncontrasting
confidence: 81%
“…Each of the questions in this questionnaire has a scale that ranges from 0 to 3, where poorer sleep quality is indicated by higher scores and the total score ranges from 0 to 21, with poor sleep quality being scores > 5 [ 43 , 44 , 45 ]. Taking into account that other studies used a cut-off score of 5 points, in the global PSQI score, to categorize people with or without sleep disorders [ 35 , 46 ]. In this research, for both groups, those evaluated were classified according to whether or not they presented with low sleeping quality (LSQ) in such a way that people with scores < 5 were categorized as without LSQ, while those with scores ≥ 5 were grouped in the with LSQ category.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, positive associations between obesity, high blood pressure and hyperglycemia with a longer duration of sleep were described in the Arab population [ 33 ]. In people with type 1 and 2 diabetes, both the amount of sleep and the quality of sleep were found to be essential for glycemic control and metabolic function [ 34 , 35 ], and some evidence suggests that lack of sleep would play an important role in the development of type 2 diabetes mellitus, mediated by obesity and by alterations in the regulation of leptin [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also identified a strong negative effect of SJL on the metabolic profile, such as increases in serum triglyceride levels [19,14], TC (14), fasting insulin and HOMA-IR, besides, decreased serum HDL levels [19], as well as elevated levels of fasting glucose [16,14], increased risk for high glycated hemoglobin [15,54] and a deterioration in glycaemic control in diabetic patients [54]. Further studies with bariatric patients over a longer follow-up should evaluate the effect of SJL on the response of metabolic markers to confirm or discard the results presented in this study.…”
Section: Discussionmentioning
confidence: 97%